Marketing Strategies for Construction Services in Facing Market Competition at PT Creative Berkat Abadi - Nailil Muna Meiliya; Trisni Handayani (Journal of Management Studies and Development, 2026)
Increasingly fierce competition in Indonesia’s construction services sector requires companies to implement comprehensive and structured marketing strategies. This study aims to analyze the implementation of PT Creative Berkat Abadi’s construction services marketing strategy in responding to market competition using the 7P marketing mix framework (Product, Price, Place, Promotion, People, Process, and Physical Evidence). The method used was descriptive qualitative research, with data collected through observation, semi-structured in-depth interviews, and documentation from three key informants selected via purposive sampling. Data analysis employed the Miles and Huberman interactive model with triangulation of techniques and sources to ensure data validity. The research results indicate that PT Creative Berkat Abadi has implemented a fairly effective marketing strategy based on trust and personal relationships, characterized by integrated services (Engineering, General Contractor, Supplier, and Maintenance), transparent real-cost-based pricing, and word-of-mouth and repeat-order mechanisms that have successfully maintained a steady flow of clients over four years of operation. However, there are strategic limitations, including a lack of digital presence, the absence of written Standard Operating Procedures, and human resource development that remains informal. This study serves as a practical reference for medium-sized construction service companies seeking to optimize their marketing mix. The company is recommended to undertake digital transformation by developing a website and business social media accounts, formalize operational processes through the creation of SOPs, and diversify marketing channels to expand market reach and enhance long-term competitiveness.